Initial Validation of the Sleep Disturbances in Pediatric Cancer Model - Daniel, Lauren C. (J Pediatr Psychol, 2016)
Objective  The current study evaluates content validity of the Sleep Disturbance in Pediatric Cancer (SDPC) model using qualitative and quantitative stakeholder input.  Methods  Parents of children (aged: 3–12 years) with acute lymphoblastic leukemia ( n  = 20) and medical providers ( n  = 6) participated in semi-structured interviews about child sleep during cancer treatment. They also rated SDPC model component importance on a 0–4 scale and selected the most relevant sleep-related intervention targets.  Results  Qualitatively, parents and providers endorsed that changes in the child’s psychosocial, environmental, and biological processes affect sleep. Stakeholders rated most model components (parent: 32 of 40; provider: 39 of 41) as important (>2) to child sleep. Parents were most interested in interventions targeting difficulty falling asleep and providers selected irregular sleep habits/scheduling, though groups did not differ significantly. Conclusions  Stakeholders supported SDPC content validity. The model will inform subsequent measure and intervention development focusing on biological and behavioral factors most salient to sleep disturbances in pediatric cancer.